The dark side of the interface: examining the influence of different background modes on cognitive performance. - Gazit, Tali; Tager-Shafrir, Tair; Zhong, Hua-Xu; Hung, Patrick C. K.; Cheung, Vien (Ergonomics, 2026)
With the pivotal role that dark mode plays in user interface design, its widespread adoption across various applications and operating systems is evident. This study aims to investigate the potential effects of different background modes (light and dark) using cognitive ability tests and collect demographic variables for analysis. A total of 173 participants from diverse geographic regions worldwide completed an online survey comprising cognitive tests. The experimental results demonstrate that cognitive scores were higher in light mode compared to dark mode. Additionally, younger adults performed significantly better than older adults in light mode, while participants with academic education scored higher than those without in dark mode. In both modes, men outperformed women. A majority of females prefer light mode, while a higher proportion of males feel comfortable with both modes. These findings address the gap in understanding the impact of dark mode, offering practical insights in inclusive design practices. Practitioner Summary: This study examines the effects of light and dark modes on cognitive performance and user preferences across different demographic variables. The results indicate that light mode generally enhances performance across all demographic groups. Males consistently outperformed females, younger adults scored higher than older adults in light mode, and participants with academic education performed better than those without in dark mode. Females preferred light mode and males were comfortable with both.